Comparing Informants for Mental Health Screening at the Preschool Level. Issue 5 (11th October 2022) - Moore, Stephanie A.; Dowdy, Erin; Fleury, Isabelle; DiStefano, Christine; Greer, Fred W.
Abstract: Universal screening for mental health in preschools provides the opportunity for early identification and early intervention, but guidance regarding which informants to use is needed. Preschoolers' ( N  = 535) parent and teacher reports across two screening forms were analyzed to determine similarities and discrepancies for classification results and screener scores. The analyses also examined whether an additional rater provided incrementally valid information to the prediction of longitudinal kindergarten outcomes. Parents' and teachers' screening scores were significantly correlated across forms by rater and across raters. However, categorical classification results indicated that teachers were more likely than parents to rate preschoolers in at-risk ranges across forms. Finally, hierarchical regression analyses revealed that teacher ratings were predictive of kindergarten social–emotional, cognitive, and academic outcomes and that the addition of parent ratings did not significantly improve prediction of outcomes. Implications are discussed in the context of multiple raters within multiple-gating screening procedures. Impact Statement Universal screening for behavioral and emotional risk is important at the preschool level because it provides a critical opportunity for early identification and early intervention. Parents and teachers who participated in universal screening demonstrated low levels of agreement in their ratings of preschool children's emotional and behavioral risk, although both are valuable informants. If the goal of screening is to predict later kindergarten academic and social–emotional outcomes, practitioners may consider collecting screening information from teachers first.